Inch-Sized Thin Metal Halide Perovskite Single-Crystal Wafers for Sensitive X-Ray Detection - Feng, Anbo; Xie, Shengdan; Fu, Xiuwei; Chen, Zhaolai; Zhu, Wei (Frontiers in Chemistry, 2022)
Metal halide perovskite single crystals are a promising candidate for X-ray detection due to their large atomic number and high carrier mobility and lifetime. However, it is still challenging to grow large-area and thin single crystals directly onto substrates to meet real-world applications. In this work, millimeter-thick and inch-sized methylammonium lead tribromide (MAPbBr3) single-crystal wafers are grown directly on indium tin oxide (ITO) substrates through controlling the distance between solution surface and substrates. The single-crystal wafers are polished and treated with O3 to achieve smooth surface, lower trap density, and better electrical properties. X-ray detectors with a high sensitivity of 632 µC Gyair−1 cm−2 under –5 V and 525 µC Gyair−1 cm−2 under –1 V bias can be achieved. This work provides an effective way to fabricate substrate-integrated, large-area, and thickness-controlled perovskite single-crystal X-ray detectors, which is instructive for developing imaging application based on perovskite single crystals.